2014
DOI: 10.1038/ncomms4128
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic enzyme expression highlights a key role for MTHFD2 and the mitochondrial folate pathway in cancer

Abstract: Metabolic remodeling is now widely regarded as a hallmark of cancer, but it is not clear whether individual metabolic strategies are frequently exploited by many tumours. Here we compare messenger RNA profiles of 1,454 metabolic enzymes across 1,981 tumours spanning 19 cancer types to identify enzymes that are consistently differentially expressed. Our meta-analysis recovers established targets of some of the most widely used chemotherapeutics, including dihydrofolate reductase, thymidylate synthase and ribonu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

25
521
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 497 publications
(548 citation statements)
references
References 47 publications
25
521
0
2
Order By: Relevance
“…The shMTHFD2 cells examined here could still grow in the absence of glycine (albeit at a slower rate), although it is not clear whether that is due to residual MTHFD2 activity in these cells, the activity of other enzymes such as 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 Fig.3). Supplementation of cell culture media with glycine was also unable to rescue cancer cells after RNAi silencing of MTHFD2 11 . The question therefore arises as to why MCF-7 cells with suppressed MTHFD2 are rendered dependent on exogenous glycine.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The shMTHFD2 cells examined here could still grow in the absence of glycine (albeit at a slower rate), although it is not clear whether that is due to residual MTHFD2 activity in these cells, the activity of other enzymes such as 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 Fig.3). Supplementation of cell culture media with glycine was also unable to rescue cancer cells after RNAi silencing of MTHFD2 11 . The question therefore arises as to why MCF-7 cells with suppressed MTHFD2 are rendered dependent on exogenous glycine.…”
Section: Discussionmentioning
confidence: 99%
“…In a separate study, investigation of 1,454 metabolic enzymes in 1,981 human tumors found MTHFD2 to be the most consistently over-expressed 11 . This study also found that MTHFD2 was not present in normal proliferating cells, but appeared to be specific to proliferating transformed cells.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…Additionally, SHMT2 was found to drive glioma cell proliferation in the presence of ischemia, making the cells sensitive to inhibition of the glycine cleavage system (Kim et al, 2015). In an analysis of differentially expressed mRNA in cancer tissues, Nilsson et al (2014) identified enzymes of the one-carbon folate pathway to be among the most differentially expressed metabolic enzymes in cancer compared with normal cells, with MTH FD2 ranking at the top of the list. In addition, MTH FD2 expression correlated with poor survival in patients with breast cancer (Liu et al, 2014;Nilsson et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…1 B). The role of folate-mediated one-carbon metabolism in cancer, especially in the mitochondrial compartment, has been a subject of renewed interest (Jain et al, 2012;Nilsson et al, 2014). A recent publication has highlighted the mitochondrial enzyme involved in one-carbon folate metabolism, MTHFD2, as the most differentially expressed enzyme in cancer cells compared with normal cells (Nilsson et al, 2014).…”
Section: Res Ults One-carbon Folate Metabolism Is a Core Pathway Altementioning
confidence: 99%